The nested hierarchy of self and its trauma: In search for a synchronic dynamic and topographical re-organization - Scalabrini, Andrea; Mucci, Clara; Northoff, Georg (Frontiers in Human Neuroscience, 2022)
The sense of self has always been a topic of high interest in both psychoanalysis and most recently in neuroscience. Nowadays there is agreement in psychoanalysis that the self emerges from the relationship with the other (e.g. the caregiver) in terms of his/her capacity to attune, regulate and synchronize with the emergent self of the infant. The outcome of this relational/intersubjective syncronization is the development of the sense of self and its regulatory processes both in dynamic psychology and in neuroscience. In this work we propose that synchrony is a fundamental bio-behavioral factor in these dialectical process between self and other that shapes the brain-body-mind system of the individuals including their sense of self. Recently in neuroscience it has been proposed by the research group around Northoff that the self is constituted by a brain-based nested hierarchical three-layer structure including interoceptive, proprio-exteroceptive and mental layers of self. This may be disrupted, though, when traumatic experiences occur. Following the three levels of trauma theorized by Mucci we here proposed how different levels of traumatic experiences might have an enduring effect in yielding a trauma-based topographic and dynamic re-organization of the nested model of self featured by dissociation. In conclusion, we propose that different levels and degrees of traumatic experience are related to corresponding disruptions in the topography and dynamic of the brain-based three layer hierarchical structure of self.